The sounds of safety: stress and danger in music perception - Schäfer, Thomas; Huron, David; Shanahan, Daniel; Sedlmeier, Peter (Frontiers in Psychology, 2015)
As with any sensory input, music might be expected to incorporate the processing of information about the safety of the environment. Little research has been done on how such processing has evolved and how different kinds of sounds may affect the experience of certain environments. In this article, we investigate if music, as a form of auditory information, can trigger the experience of safety. We hypothesized that (1) there should be an optimal, subjectively preferred degree of information density of musical sounds, at which safety-related information can be processed optimally; (2) any deviation from the optimum, that is, both higher and lower levels of information density, should elicit experiences of higher stress and danger; and (3) in general, sonic scenarios with music should reduce experiences of stress and danger more than other scenarios. In Experiment 1, the information density of short music-like rhythmic stimuli was manipulated via their tempo. In an initial session, listeners adjusted the tempo of the stimuli to what they deemed an appropriate tempo. In an ensuing session, the same listeners judged their experienced stress and danger in response to the same stimuli, as well as stimuli exhibiting tempo variants. Results are consistent with the existence of an optimum information density for a given rhythm; the preferred tempo decreased for increasingly complex rhythms. The hypothesis that any deviation from the optimum would lead to experiences of higher stress and danger was only partly fit by the data. In Experiment 2, listeners should indicate their experience of stress and danger in response to different sonic scenarios: music, natural sounds, and silence. As expected, the music scenarios were associated with lowest stress and danger whereas both natural sounds and silence resulted in higher stress and danger. Overall, the results largely fit the hypothesis that music seemingly carries safety-related information about the environment.